La vie affective des objets. Sur quelques reliques de l’atelier d’Ingres - Clara Lespessailles (Les Cahiers de l'École du Louvre)
Thinking of Ingres’ studio as a family, as a cognitive and social structure, generates de facto multiple affective universes between the protagonists. Bonds between people, with works in which these bonds crystallise, as well as objects. This space, oddly devoid of any known visual representation, has forged itself in the collective imagination as a place that is both mythical and enigmatic, giving it an of aura, as much for the actors who have evolved there, for the teaching that has been allocated to it, as for the objects that have been kept and exchanged there. The studio is thus transcended and invaded by a mythical material. It becomes a sacred place where the students’ well-known devotion to the master seems to be transferred to the objects that once belonged to him. This participation in the construction of the artist’s myth is manifested in the singular fetishism attributed to the creative space and, ultimately, to the objects within it. Through the study of two specific cases of “Ingraliae”, we will highlight the relationship of filiation existing between Ingres and his pupils through “objects” of a memorial and affective nature. The first of these objects is an armchair that once belonged to the master and was kept by Paul Chenavard, a pupil of Ingres who later moved into his studio; the second object is a plaster cast of Ingres’ hand, made around 1840. One of the casts in the Musée Rolin in Autun was donated by Eugène Froment, a pupil of Amaury-Duval.